IMAGE PROCESSING METHOD TO DETECT THE POSITION OF VANNAMEI SHRIMP IN MUDDY WATERS - Waryanto, Waryanto; Setiawan, Joga Dharma; Arianto, Mochammad; Sedayu, Bakti Berlyanto; Hartanti, Ninik Umi; Suyono, Suyono; Dina, Karina Farkha; Alamsyah, Heru Kurniawan; Aziz, Hozin; Taukhid, Imam; Supriyanto, Supriyanto; Zulkarnain, Riza; Siregar, Zaenal Arifin (Agency for Marine and Fisheries Extension and Human Resources, 2025)
One way to help the feeding process vannamei shrimp in ponds that have cloudy surface using constructed with a size of 50 × 50 × 18 cm with a water height in the pond of 7 cm from bottom, where the data in the form of images was obtained from data collection 25 times using a camera is placed at a height of 52 cm above the water surface. The pond’s entire surface was captured with one click of the camera. The number of vannamei shrimp used in this study was 7. The method used for data processing is thresholding, in which the threshold value is generated using a histogram-based technique from the image data. This method is employed to distinguish shrimp from non-shrimp regions in the image. From this study, a vannamei shrimp detection technique was developed, producing results in the form of a script that distinguishes vannamei shrimp objects from non-vannamei shrimp. The detection accuracy achieved using the thresholding method in this study is 94.28%. The positions of the shrimp were produced in the form of coordinates as a step to success according to the objectives of this study, which were able to detect positions, in order to help facilitate the process of feeding in ponds. This detection technique could be developed for application on full-scale ponds, utilizing cameras mounted on drones as a tool for detecting vannamei shrimp positions in cloudy pond water. This technology may be adapted to allow targeted feeding of shrimp in ponds, thus maximizing food consumption and minimizing food wastage.